Kesiapan Adopsi Blockchain: Perspektif Pakar tentang Kebijakan, Implementasi, dan Tata Kelola di Indonesia - Juan Mikael Simatupang; Etin Indrayani (Jurnal Bina Praja, 2025)
Indonesia faces serious cybersecurity challenges due to its centralized data systems, which are vulnerable to attack. Blockchain technology offers potential solutions through its decentralized, immutable, and transparent architecture. This study examines the readiness for blockchain adoption in Indonesia using a qualitative approach through in-depth interviews with purposively selected experts from government, academia, and non-governmental organizations. The results indicate that the fundamental challenges are non-technical. Legally, blockchain’s immutable nature conflicts with citizens’ right to delete personal data, while policy-wise, the principle of decentralization is inconsistent with the government’s mandate for data centralization. The findings suggest that the primary obstacles are not technical issues, but rather a lack of political will, bureaucratic resistance, and budget constraints. Therefore, the most realistic solution for Indonesia is the implementation of a permissioned blockchain model. This model must be designed with privacy-by-design principles and must comply with national cybersecurity standards to be implemented amidst existing legal and policy challenges.